(untitled) (Research, Society and Development, 2022)
Objective: to evaluate nursing interventions in pain management in newborns hospitalized in Neonatal Intensive Care Units. Methodology: this is an integrative literature review, carried out in the CINAHL, PUBMED and MEDLINE databases. Original articles available in full, published between 2012 and 2021, in Portuguese, English and Spanish, with at least one nurse among the authors or participants of the intervention, were included in the study. Controlled descriptors were used: pain, neonatal nursing, newborns and intensive care unit. Results: regarding nursing interventions in the management of pain in newborns, there was a higher prevalence of the use of non-pharmacological measures, highlighting the non-nutritive sucking and the use of oral sucrose solution. Discussion: there is unanimity of studies referring to pain management by the nursing team regarding the non-use of pain assessment scale in clinical practice. This attitude was justified by the assessment carried out based on physiological indicators, facilitated by the individual experiences and experiences of each professional and by the lack of a standard or protocol for pain assessment and management in the neonatal institution. Conclusion: the applicability of interventions has been shown to be a great challenge due to the empirical assessment of pain by some teams. Raising at varying levels of dissatisfaction with the quality of care provided to the newborn with regard to pain management.